'Santa baby, hurry [extra carefully] down the chimney tonight' – Prevalence of Christmas related injuries 2007–2016 in the United States: Observational study. Issue 1 (March 2019) - Lauche, Romy; Wardle, Jon; Peng, Wenbo; Adams, Jon; Cramer, Holger
Abstract: Objectives: To assess the prevalence of Christmas-related injuries for Santa Claus, Santa's helpers, Santa impersonators and Christmas revellers. Methods: Data were obtained from the US using National Electronic Injury Surveillance System (NEISS), a national probability sample of U.S. hospitals with 24-hour accident and emergency services. Data from 2007 to 2016 were analysed regarding emergency visits involving injuries related to Christmas products, and weighted prevalence and patterns of Christmas-related injuries were reported. Results: No injuries directly affecting Santa Claus, Santa Claus' helpers, or Santa impersonators were identified. U.S.-wide, 277 children were injured by Santa impersonators. Further injuries were reported in association with artificial Christmas trees (17, 928 injuries), real Christmas trees (2216 injuries), Christmas tree stands/supports (2839 Injuries), tree lights (31, 855 injuries), electrical decorations (36, 054 injuries), non-electrical decorations (80, 208 injuries), and Christmas presents (2305 injuries). Almost all injuries occurred in Caucasians and injuries were most common in children, adults aged 30–60, and in those aged 70 or older. Injuries related to electrical Christmas decorations were more common in males; those related to non-electrical Christmas decorations were more common in females. Conclusions: Despite inherent dangers associated with his work, Santa Claus appears to be safe and is not responsible for Christmas-related injuries. In contrast, the considerable safety hazards of Santa impersonation practices and Christmas products require further investigation.